The Impact of Public Activity Restriction during COVID-19 to Air Quality in Urban Area of Bandung Measured Using Mobile Monitoring - Martin Adrian; Puji Lestari; Ferry Iskandar; Muhammad Miftahul Munir (Aerosol and Air Quality Research)
Abstract The COVID-19 outbreak impacted the people’s lives in the world. Lockdown is one way of controlling the spread of the virus. In Indonesia, the government would rather implement public activity restriction than lockdown. The detailed comprehension of the effect of lockdown or similar policies on air pollution is valuable for making future policies about the control of pandemics as well as its effect on air quality. To understand the effect of public activity restriction (PAR) and its correlation with air pollution, mobile monitoring (MM) of particulate matter (PM2.5) was performed in the urban area of Bandung, Indonesia, in July 2021. Based on MM using a bicycle, we found that a PAR had an impact on air pollution. Our result showed that there was a decrease between 20% and 30% in 3 of 6 sub-districts. The advantage of MM was highlighted by the prominent visualization of the concentration of PM2.5 MM data at the level of the road. Localization of polluted roads could be seen clearly through the MM method. The uncovering effect of PAR on air pollution using the MM method will provide important insights for government and policymakers to develop future policy that controls air pollution for better citizen health.